3‐Hydroxypicolinic Acid as an Effective Matrix for Sophorolipid Structural Elucidation Using Matrix‐Assisted Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry. Issue 3 (7th February 2020) - Yatim, Abdul Rashid M.; Wan Muhammad Zulkifli, Wan Nur Fatihah; Majid, Amin Malik Shah; Foster, John L.; Hayes, Douglas G.
Abstract: Determination of the distribution of sophorolipid (SL) congeners controls their self‐assembly structures and therefore their employment as glycolipid biosurfactants in cosmetics, environmental remediation, and personal care applications. The compatibility of 3‐hydroxypicolinic acid (HPA) as a matrix for compositional analysis of SL using palm olein as carbon energy source by matrix‐assisted laser desorption ionization time of flight mass spectrometry (MALDI‐TOF MS) analysis under positive and negative ion modes is studied in this work. Examination in positive ion mode revealed ions that were not detected in negative ion mode. Molecular ions produced using HPA matrix were lactonic Glc‐Glc‐1′, 4″‐C18:1, anionic Glc‐Glc‐1′‐C18:1, lactonic monoacetate of Glc‐Glc‐1′, 4″‐C18:1, and anionic monoacetate Glc‐Glc‐1′‐C18:1 and the anionic diacetate of Glc‐Glc‐1′‐C18:1. We also detected Glc‐Glc‐1′‐C18:0, GlcOAc‐Glc‐1′‐C18:0, GlcOAc‐GlcOAc‐1′, 4″‐C18:0, and GlcOAc—GlcOAc‐1′‐C18:0 which are congeners of SL with stearic acid moieties. 3‐HPA has been established to be the superior matrix for elucidation of structures for SL using MALDI‐TOF MS.